Enhancing Didactics to Address Student Concepts and Chaos of Events: A Scientific Perspective (The Peerian Journal, 2023)
Effective teaching requires an understanding of students' pre-existing concepts and the ability to manage the chaotic nature of educational environments. This scientific article explores the significance of didactics, the science of teaching and learning, in addressing the challenges associated with student concepts and the chaos of events. By embracing evidencebased and student-centered instructional practices, educators can create an engaging learning environment that promotes conceptual understanding and minimizes confusion. This article aims to provide insights and practical suggestions for educators to enhance their didactic strategies in order to counteract student misconceptions and navigate unpredictable events.